Rooting depth and xylem vulnerability are independent woody plant traits jointly selected by aridity, seasonality, and water table depth - Laughlin, Daniel C (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © 2023 New Phytologist Foundation.